Utilization of Business Intelligence to Improve Operational Efficiency of SMEs in Lampung - Tiara Prisca Sabilla; Rinaldi Bursan (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
In light of the moderating effects of organizational readiness (OR) and digital literacy (DL), this study attempts to examine how business intelligence (BI) affects the sustainable performance and decision-making quality of SMEs in Lampung Province.  This study used a convergent parallel design and a mixed methods approach, integrating both qualitative and quantitative data to offer a thorough insight.  In-depth interviews with 15 important informants provided qualitative data, while purposive sampling was used to choose 200 SMEs as respondents for quantitative data. The outer and inner models were evaluated in a quantitative study using Partial Least Squares Structural Equation Modeling (PLS-SEM), and thematic analysis was used to examine the qualitative data. The findings demonstrated that BI significantly influences sustainable performance (β=0.24, p<0.001) and decision quality (β=0.65, p<0.001), both directly and via decision quality mediation (β=0.58, p<0.001). The association between BI and decision quality was found to be strengthened by OR and DL.  SME players stress the significance of rapid, precise, and integrated data access in enhancing the precision of company strategy, and qualitative findings corroborate the quantitative findings. This study offers useful suggestions for boosting SMEs' competitiveness in the age of digital transformation.